Robot-assisted vesical neck h-shaped flap plasty for vesicourethral anastomotic stenosis: a case report - Xiao, Xingyuan; Wang, Kuibiao; Yu, Qiuxuan; Yin, Hang; Lu, Mengxin; Gao, Xincheng; Li, Bing (AME Case Reports, 2026)
Background: Vesicourethral anastomotic stenosis (VUAS) is a challenging complication, occurring in 2%–7% of patients following radical prostatectomy. Endoscopic treatment fails in some patients, severely impairing their quality of life. Open reconstructive surgery is technically demanding with a long learning curve. Thus, to address a complication known as vesicourethral anastomotic stenosis following radical prostatectomy, we propose a new robot-assisted vesical neck H-shaped plasty.Case Description: A 57-year-old patient with prostate cancer developed vesicourethral anastomotic stenosis (with a stenosis segment length of 2 cm) 4 months after laparoscopic radical prostatectomy. Following short-term recurrence of the condition after three transurethral incisions for VUAS, the patient received robot-assisted vesical neck H-shaped plasty for posterior urethral reconstruction. The surgical technique primarily involves constructing an H-shaped bladder flap, tubularizing it to reconstruct a funnel-shaped posterior urethra, performing a tension-free anastomosis between the vesical neck and the posterior urethra, and constructing a retrocurvature structure of the urethra. Treatment success was defined by both anatomical and functional criteria, unobstructed passage of a 17 Fr cystoscope or a urinary flow rate >15 mL/s. The patient in this study achieved adequate early urinary patency and no related complications.Conclusions: Based on short-term follow-up, robot-assisted vesical neck H-shaped flap plasty is feasible for vesicourethral anastomotic stenosis, but long-term follow-up is needed for verification.